What predicts climate concern and pro-environmental behavior? Case study on Eastern Hungarian settlement. - Kiss, Emőke; Mester, Tamás; Balla, Dániel (Bulletin of Geography. Socio-economic Series, 2025)
The study examined climate concern (CC) and pro-environmental behaviour (PEB) regarding climate change. In our research, we chose the second largest city in Hungary, Debrecen. We conducted a questionnaire survey among residents in 2020 (N = 200). The closeness, strength and intensity of the relationship between the predictors, Total Climate Concern Index (TCCI) and PEB Index (PEBI), were examined by correlational analyses. Regression analysis investigated selected variables’ relative impacts on and relationships to TCCI and PEBI. We revealed that the TCCI of inhabitants is very high, but PEBI is much lower. In correlational analyses, TCCI and PEBI were each separately found to correlate positively and significantly with AI (Attitude Index, which comprises risk perception and confident willingness to change lifestyle). ...